SIMULASI PERGERAKAN TINGKAT BUNGA BERDASARKAN MODEL VASICEK - Shantika Martha; Dadan Kusnandar; Naomi N. Debataraja (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2015)
Interest rate movements that change over time can be viewed as a stochastic process for continuous time. One model of interest rate movement for a continuous time is the Vasicek model. This study aims to describe the characteristics of interest rate movements based on the Vasicek model. In Vasicek model there are three parameters, k, θ, and σ. Based on the simulation result, it is seen that interest rate movement based on Vasicek model is mean reversion (tend to be around θ). The greater the value of k then the process of interest rate will be faster towards θ. While the greater the value of σ then the process will further deviate from θ.